In situ HT-ESEM study of crystallites growth within CeO2 microspheres. Issue 10 (December 2015) - Nkou Bouala, G.I.; Clavier, N.; Léchelle, J.; Mesbah, A.; Dacheux, N.; Podor, R.
Abstract: Cerium dioxide is widely studied due to its potential interest in several applications, including heterogeneous catalysis. In this field, modifications of the crystallographic orientations and surface reactivity of CeO2 can lead to activity loss of metal supported catalysts. In situ High Temperature-Environmental Scanning Electron Microscopy observations were then developed to monitor such evolution in CeO2 spherical particles. Microspheres with 300–800 nm diameter were heat treated for 1–120 min in the 1000–1200 °C range. Subsequent image analysis led to monitor and quantify the crystallite growth during isotherm dwells. Two distinct mechanisms controlling the growth of crystallites in a single microsphere were then evidenced depending on the heating duration, i.e. oriented attachment then diffusion. Precise control of the aggregates inner structure (number of crystallites and density) was also achieved and described as a nanostructure map. These results pave the way to new opportunities in nanoparticle design.